2004
DOI: 10.1097/01.ico.0000134195.71981.e2
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Study of Anterior Lens Capsule Allotransplants in Chronic Corneal Ulcers

Abstract: On the ultrastructural level, anterior lens capsule allotransplants in mechanically induced corneal ulcer heal with continuously formed epithelial basement membrane and numerous hemidesmosomes. This enables significant reformation of hemidesmosomes that are identical in size to hemidesmosomes in healthy corneas and helps forming a stronger apposition for epithelial cells to underlying structures in eyes where epithelial basement membrane has been destroyed from chronic ulceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…Meanwhile, studies have demonstrated that HALC is a good substrate for cultivation of corneal epithelial cells and retinal pigment epithelial cells. 19,20 Therefore, HALC might also be an alternative to the Descemet membrane as an HCEC carrier. The aim of this work was to evaluate the general feasibility of using HALC as a scaffold for expansion and transplantation of HCECs.…”
mentioning
confidence: 99%
“…Meanwhile, studies have demonstrated that HALC is a good substrate for cultivation of corneal epithelial cells and retinal pigment epithelial cells. 19,20 Therefore, HALC might also be an alternative to the Descemet membrane as an HCEC carrier. The aim of this work was to evaluate the general feasibility of using HALC as a scaffold for expansion and transplantation of HCECs.…”
mentioning
confidence: 99%
“…13 The wound healing process after filtration surgery is a series of complicated biological reactions, which include sludged blood formation period, proliferation period, granuloma formation period, and collagen formation period. In patients without high risk factor for failure, the migration and proliferation of fibroblasts postoperatively culminate in 3-5 days and terminate in 11 days.…”
Section: Discussionmentioning
confidence: 99%
“…Use of ALC graft for chronic corneal ulcers or as support material in RPE cell transplantation has been well described in literature. [9][10][11][12] ALC transplantation has been shown to be effective in resolution of these problems. It does not result in fibrosis or rejection reaction, and components of humoral immunity do not participate in immune reaction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations